Efficacy of Photo biomodulation Therapy Compared with Hyaluronic Acid Injections in Temporomandibular Disorder Treatment: A Systematic Review - Ebenezer, Vijay; Sinha, Parijat; Ramalingam, Balakrishnan; Nithyasundar, Kannan; Priya, R Swarna; Natarajan, Prabhu Manickam (Bangladesh Journal of Medical Science, 2026)
BACKGROUND Temporomandibular Disorder (TMD) has been postulated as a condition of multifactorial aetiology, usually resulting from muscle hyperfunction or parafunction, traumatic sources, hormonal impact, and alterations in the structure of the joint. Treatment modalities for management are numerous and include the invasive and non-invasive modalities. Photo biomodulation therapy is a non-pharmacologic and non-invasive treatment which has been found to have positive impacts in the treatment while intra articular injections with or without arthrocentesis is a minimally invasive procedure but is very potent in alleviating pain and inflammatory signs. METHODS The current review was carried out in the context of PRISMA guidelines. A systematic search in PubMed, Google Scholar, Wiley library, Cochrane library databases, Scopus and grey literature was done for the published studies between 1st January 2003 and 1st October 2023. For randomized controlled trials, quality assessment was done with the help of Cochrane risk of bias tool (ROB-2) using Review Manager 5.4.1 RESULTS Through search strategy 76 articles were yielded. After screening through titles and abstracts, 55 articles were excluded and finally 21 articles were included in this review. CONCLUSION In conclusion Photo biomodulation is found to be effective in reducing pain, mean mouth opening in the treatment of temporomandibular disorder when compared to hyaluronic acid, however this systematic review acts as a scoping review to conduct more comparative studies to obtain an evidence-based analysis. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S26-S35